Has the Resignation of Independent Directors Holding Government Positions Improved Firm Performance?—A Quasi-Natural Experiment From China - Zhang, Tingting; Li, Yanxi; Hou, Deshuai (Frontiers in Psychology, 2022)
The Organization Department of the Communist Party of China (CPC) announced the Opinions on Further Regulation on Party and Political Leaders and Cadres Working Part-Time (Holding Offices) in Enterprises to force the resignation of government officials holding the position of independent director in listed companies (GID). This paper empirically examines the impact of the GID resignation on firm performance using a difference-in-differences (DID) model, which is an exogenous event with a "natural experiment". The study finds that after the promulgation of the Opinions, firms that lose some of their political resources and their corporate performance decreases significantly compared to firms that do not experience GID resignations. A good external governance environment, while somewhat weakening, is not sufficient to offset the negative impact of the loss of political resources on firm performance. This paper further explores the mechanism by which the GID resignation affects firm performance: one important way in which the resignation of GIDs cause the loss of political resources on which the firm's development depends is that the loss of the firm's tax benefits after GID resignation directly leads to a decline in performance; it also leads to a reduction in the firm's financial subsidy income and a reduction in the amount of bank loans, but both of these do not have a significant effect on the decline in firm performance. The study suggests that GIDs play more of a resource-providing "official" role than an "independent director's" supervisory and advisory role in Chinese listed companies. The findings of this paper reveal the phenomenon of "Political-Business Spin" in China, which has some implications for developing countries, represented by China, to improve the independence of the board of directors and the corporate governance.